Sekuritisasi Presiden Immanuel Macron Terhadap Imigran Muslim Melalui Undang-Undang Anti-Separatisme Perancis - Nida Saidathul Iza; Mohammad Rosyidin; Reni Windiani (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
In response to the issue of Muslim immigrants, a controversial policy has been issued by France. President Immanuel Macron issued a policy to respond to the increasing number of cases of extremism and terrorism in various regions of France and became one of the instruments of regional security. Macron addressed the issue by issuing a speech to shape perceptions of the threat posed by the issue of Muslim immigrants. So that in the end the policies formed by Macron were successfully accepted by the public and officially ratified. It is interesting to study how the political elites in a country shape the perception of an issue so that in the end the issue gets support from the community. This study will analyze this by using the key question